Reconstruction of the Spanish Conquest by Tariq bin Ziyad: A Critical Historiographical Analysis in a Global Historical Perspective - Jusmiati Jusmiati; Hasaruddin Hasaruddin; Syamzan Syukur (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to reconstruct the Spanish conquest by Tariq ibn Ziyad in 711 CE through a global historical and critical historiographic approach. This study is motivated by the dominance of classical historiographic narratives that tend to present the conquest as a mere heroic story, without considering the complexity of the social, political, and geopolitical contexts that underlie it. This study uses a qualitative method with a historical-critical approach through literature study, source criticism, and comparative analysis of Islamic and Western historical narratives. The results show that the Spanish conquest was not merely a military expansion, but part of the geopolitical dynamics of the Mediterranean region influenced by the internal crisis of the Visigoth Kingdom, adaptive military strategies, and social interactions with local communities. In addition, this event had a significant impact on shaping the interconnectedness of civilization between the Islamic and Western worlds, particularly in the fields of science, culture, and politics. Thus, this conquest needs to be understood as a multidimensional and interconnected historical process. This research emphasizes the importance of a critical historiographic approach and a global perspective in the study of Islamic history to produce a more contextual, integrative understanding, free from narrative simplification.